Congenital Absence of the Nails: A Variant of Cooks Syndrome - N. Rishana; Murali Narasimhan; Ramachandran Ramakrishnan; A. K. Mohamed Abdullah (Indian Journal of Paediatric Dermatology)
Congenital anonychia is a rare condition which is characterized by the absence of multiple nails or the whole fingernails, toenails, or both. It occurs due to autosomal dominant or recessive inheritance. Normal skin at sites of missing nails and absence of distal phalanges on radiography are features. We present a case of Cooks syndrome variant in a 9-month-old female child who had loss of toe nails and brachydactyly with typical radiological findings.